Brain Drain or Brain Exchange: Developing Country Implications - Altbach, Philip (International Higher Education, 2013)
Many industrialized countries are looking to keep foreign graduates to fill jobs for which there are shortages. This article argues that these practices are a continuation of the "brain drain." The developing world is subsidizing the economies of the rich nations.